Parametric Investigation of a Form Tool Wear and Dimensional Inaccuracy in Turning Operation of AISI 1045 - Hayat, A.; Amjad, M.; Mufti, N. A.; Shoaib, M. (The Nucleus, 2016)
In any manufacturing setup, turning operation is the most frequently used metal cutting process especially for axis symmetric circular parts. This paper reports the effects and optimization of two process parameters (feed rate & cutting speed) on two response factors (tool wear & dimensional inaccuracy) in turning operation of aplain carbon steel AISI 1045. Flat form tool of high speed steel (HSS) having various profiles has been used for turning operation. The experimentation is done under varying cutting conditions by changing the feed rate and cutting speed on a precision lathe machine using plain carbon steel of finished diameter 30mm as work piece material each time. Optimal settings of the process parameter are achieved using response surface methodology (RSM). Analysis of variance (ANOVA) is used to identify the significance of control factors. It is found that the most significant factor which affects the tool wear and dimensional inaccuracy is the feed rate.